Headache yesterday in China: A new approach to estimating the burden of headache, applied in a general-population survey in China. (November 2013) - Yu, Shengyuan; He, Mianwang; Liu, Ruozhuo; Feng, Jiachun; Qiao, Xiangyang; Yang, Xiaosu; Cao, Xiutang; Zhao, Gang; Fang, Yannan; Steiner, Timothy J
Background: In order to minimize recall bias in burden estimation, questions about headache yesterday were included in a population-based survey initiated by Lifting The Burden : The Global Campaign against Headache. Methods: Throughout China, nonrelated respondents aged 18–65 years were randomly sampled from the general population by a door-to-door survey. A validated structured questionnaire included inquiry into occurrence and burden of headache on the preceding day ("headache yesterday"). Results: The participation rate was 94.1%. Of 5041 participants, 286 (5.7%) (male 3.6%, female 7.9%) reported headache yesterday. Age-weighted prevalence of headache yesterday was 4.8% (male 3.0%, female 6.6%). Headache yesterday lasted all day in 36.8%, <1 hour in 14.3% and for a mean of 3.7 ± 3.3 hours in 48.9%. Headache yesterday was moderate to severe in 79.9%; disability such that they could do less than half of what they had expected was reported by 19.9% and such that they could do nothing by a further 7.5% (total 27.4%). Almost three-quarters (71.5%) with headache yesterday took medication to treat it. Conclusions: Of the adult Chinese population, 1.8% have headache at any one time that is of moderate to severe intensity in 1.4%, and 1.3% lose the equivalent of a whole day to headache-attributed disability every day. In China this means 12.3 million people.